AB0321 Predicting the Need for Rescue Medication Using Baseline Variables: Evidence from Rheumatoid Arthritis (RA) Patients in the Sarilumab Mobility Phase 3 Trial. (9th June 2015) - Strand, V.; Rendas-Baum, R.; Chen, C.; Joseph, G.; Graham, N.; Van Hoogstraten, H.; Genovese, M.C.; Huizenga, T.
Abstract : Background: RA patients may require additional medication or increased doses to successfully manage active disease. The ability to identify variables that predict this need could result in more effective treatment. Objectives: To identify baseline predictors for rescue medication in the intent-to-treat population (N=1, 197) enrolled in MOBILITY. Methods: Patients were randomized 1:1:1 to receive placebo+MTX, sarilumab 150mg every 2 wks (q2wk)+MTX or 200mg q2wk+MTX. Outcomes were assessed at baseline, every 4 wk from wk 2 –28; every 8 thereafter to wk 52. On or after wk 16, patients with <20% improvement in either SJC or TJC for 2 consecutive visits were rescued with sarilumab 200mg q2wk. Patients were classified as: 1) no rescue; 2) early rescue - wk 16; 3) late rescue - wks 20 to 52. A multinomial logistic model (MLM) was used to estimate the impact of treatment on rescue medication status (none/early/late), then to examine the ability of each baseline variable to predict rescue independent of treatment. Models used baseline variables: (n=27) demographic and disease characteristics, clinical measures and patient-reported outcomes (PROs); treatment arm and interactions between baseline variables and treatments as predictors of rescue status. Variables significant at P<0.05 were included in multivariate MLMs. Results: 940 patients never received rescue medication, 153 were rescued early and 104 between wks 20 – 52. The percentages of no, early and late rescued patients were 61%, 15% and 24% for placebo; sarilumab 150mg: 86%, 6% and 8% and 200mg: 89%, 4% and 7%, respectively. Baseline SJC, TJC, DAS28, SDAI, CDAI, SF-36 Vitality (VT) domain and FACIT-Fatigue (FACIT-F) scores independently predicted the need for rescue medication. In MLMs, treatment group, DAS28, SF-36 VT and FACIT scores were most strongly associated with rescue. Estimated odds ratios (OR) for early rescue vs no rescue for placebo patients were 4.6/5.2 times higher than for sarilumab 150mg/200mg. 2 and 4 point higher baseline DAS28 scores were associated with 78%/218% increases in OR for "early rescue"; 5 and 10 point lower SF-36 VT scores with 5% and 10% increased OR. 5 and 10 lower scores in FACIT increased the OR for early rescue by 7% and 13%. Conclusions: Sarilumab treatment lowered the odds for requiring early and late rescue. DAS28 scores and PROs of pep, energy and fatigue predicted the need for rescue among MOBILITY patients across all treatment arms, highest in placebo. These results may help clinicians to better target RA therapy. Acknowledgements: The study was sponsored by Sanofi and Regeneron Pharmaceuticals Inc. Editorial support was provided by Jennifer Dunphy of Optum and was funded by Sanofi and Regeneron Pharmaceuticals Inc. Disclosure of Interest: V. Strand Consultant for: AbbVie, Afferent, Amgen, Biogen Idec, Bioventus, BMS, Carbylan, Celgene, Celltrion, Consortium of Rheumatology Researchers of North America (CORRONA), Crescendo, Genentech/Roche, GSK, Hospira, Iroko, Janssen, Lilly, Merck, Novartis, Pfizer, Regeneron, Sanofi, SKK, Takeda, UCB, Vertex, R. Rendas-Baum Consultant for: Sanofi, Regeneron Pharmaceuticals, C. Chen Employee of: Regeneron Pharmaceuticals, G. Joseph Shareholder of: Amgen Inc., Pfizer Inc., Employee of: Sanofi, N. Graham Shareholder of: Regeneron Pharmaceuticals, Employee of: Regeneron Pharmaceuticals, H. Van Hoogstraten Employee of: Sanofi, M. Genovese Grant/research support from: Sanofi, Regeneron Pharmaceuticals, Eli Lilly, Consultant for: Sanofi, Regeneron Pharmaceuticals, Eli Lilly, T. Huizenga Consultant for: Merck, UCB, Bristol Myers Squibb, Biotest AG, Pfizer, Novartis, Roche, Sanofi-Aventis, Abbott, Crescendo Bioscience, Nycomed, Boeringher, Takeda, Zydus, and Eli Lilly, Speakers bureau: Merck, UCB, Bristol Myers Squibb, Biotest AG, Pfizer, Novartis, Roche, Sanofi-Aventis, Abbott, Crescendo Bioscience, Nycomed, Boeringher, Takeda, Zydus, and Eli Lilly